2014
DOI: 10.1001/jamaophthalmol.2013.5696
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Age-Related Macular Degeneration, Alzheimer Disease, and Dementia

Abstract: IMPORTANCEThe potential association between age-related macular degeneration (AMD) and Alzheimer disease (AD) is uncertain and has implications for understanding disease pathogenesis, referral, and treatments.OBJECTIVES To determine whether individuals admitted to the hospital with AMD were significantly more or less likely to develop AD or dementia in the following years, as well as to assess whether people with AD or dementia were significantly more or less likely to be admitted to the hospital for AMD treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 25 publications
3
83
0
3
Order By: Relevance
“…This may be because people with dementia may be less likely to attend regular appointments or to notice or report relevant symptoms and they may be more reliant on carers to manage and facilitate appointments. 117 Our study supports the idea that people with dementia often lack candidacy and may be reliant on family carers to facilitate continuity and access. This clearly has implications for people with dementia who live alone or who do not have family support.…”
Section: Access To Caresupporting
confidence: 82%
See 3 more Smart Citations
“…This may be because people with dementia may be less likely to attend regular appointments or to notice or report relevant symptoms and they may be more reliant on carers to manage and facilitate appointments. 117 Our study supports the idea that people with dementia often lack candidacy and may be reliant on family carers to facilitate continuity and access. This clearly has implications for people with dementia who live alone or who do not have family support.…”
Section: Access To Caresupporting
confidence: 82%
“…Eleven studies 98,110,117,118,123,129,136,139,145,155,161 compared access to treatment or receipt of services in groups with and without dementia. Ten 98,110,117,118,129,136,139,145,155,161 of the 11 studies found some evidence that people with dementia were less likely to receive the same quality of care or access to services as those without dementia.…”
Section: Comprehensiveness and Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, cognitive decline may be accelerated in older people with type 2 diabetes [9,10]. Moreover, the presence of dementia may adversely affect and complicate the clinical care of other conditions and be a key factor in how patients' needs are anticipated and specialist and emergency services are used [11,12]. It may also undermine patients' abilities to selfmanage chronic conditions and engage in health maintenance activities [13].…”
Section: Introductionmentioning
confidence: 99%